1991
DOI: 10.1177/002199839102500906
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Impact Failure of Continuous Fiber Reinforced Thermoplastic and Thermoset Composites

Abstract: An effort was made to study the damage mechanisms in both thermoplastic and thermoset composites in response to repeated low-velocity impacts. An instrumented falling-dart impact tester was used that provided the load-deflection and energy-deflection curves plus other numerical data on material properties. Both poly(phenylene sulfide) (PPS) and epoxy composites prepared from different preform styles and stacking sequences were tested. For any composite with given dimensions a threshold incident impact energy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…[7]. Numerous papers were published on the subject of impact fatigue and have encompassed a variety of materials such as concrete [8,9], metals [10,11], polymers [12][13][14][15] and fiber reinforced plastics [5,[16][17][18][19][20]. Each of these works was performed in totally different testing conditions (test configuration, stress state, etc.)…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[7]. Numerous papers were published on the subject of impact fatigue and have encompassed a variety of materials such as concrete [8,9], metals [10,11], polymers [12][13][14][15] and fiber reinforced plastics [5,[16][17][18][19][20]. Each of these works was performed in totally different testing conditions (test configuration, stress state, etc.)…”
mentioning
confidence: 99%
“…Some authors consider repeated impact as a convenient method for assessing the damage tolerance of composites [20]. Repeated impact tests performed by Jang et al [20] show that for a given composite laminate, there exists a threshold incident energy above which a significant damage in the form of a delamination crack will occur in the composite in response to just one impact.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively few studies have been directed towards the problem of repeated impact or impact fatigue of laminated composites and the corresponding damage mechanism. Again also here most studies reported in literature are related to CFRP [29][30][31][32][33]. Rotem [30] showed that when a low energy impact was exerted on a laminate, invisible damage might occur as a result of contact stresses between impactor and the laminate.…”
Section: Introductionmentioning
confidence: 99%
“…When impacts were repeated, the damage zone grew and caused a reduction in strength and modulus. Jang et al [31,32] studied the damage mechanisms in response to repeated low-velocity impacts in both thermoplastic (Polyphenylene sulphide, PPS) and thermoset (epoxy) composites reinforced with glass, aramid and carbon fibres. For any composite an incident impact energy threshold could be identified above which delamination would occur at the first impact.…”
Section: Introductionmentioning
confidence: 99%